An Analysis of Consumers’ Preferred Attributes of COK-KIS Products - Pitaloka, Vidya; Tambunan, Damelina B. (KnE Social Sciences, 2021)
The increase in competition is felt by pastry producers. COK-KIS, established in 2016, needs to increase their sales by improving their products using the attributes that are preferred by potential consumers, in terms of flavor, nutritional value, and packaging. However, previous studies examining these attributes have been inconsistent. Hence, the aim of the study was to examine the combination of attributes to be used in COK-KIS products that are in line with the consumer’s preferences. The data was collected from 97 respondents through purposive sampling. The results were analyzed using conjoint analysis by SPSS. The study showed that the consumers’ preferred attribute was taste, the second was the nutritional value, and the third was the packaging. The most preferred combination of attributes was the low-calorie savory product, packed in a paper bag. Keywords: consumer preferences, snacks, products, taste, packaging, nutritional value, conjoint analysis